PENANAMAN NILAI-NILAI KEJUJURAN MELALUI MEDIA KANTIN KEJUJURAN DI PONDOK PESANTREN AL HIKMAH SEMARANG - Fitria Martanti (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2017)
Educational institutions both formal, informal and informal are basically not only obliged toimprove academic quality, but also responsible in shaping the character of learners.Pesantren as an Islamic education institution obviously has a big share in building the nextgeneration of the nation. The next generation of the quality of the nation is shown by theincrease in knowledge and the change of attitude and good personality. Good personality oneof them can be seen from the honest nature owned by the students who study in boardingschool. Cafeteria as a place to buy a goods needs students and students basically not only asa place for students or students to eat or drink it, but more than that because students andstudents who are directly in contact with the canteen, the canteen is a medium that isappropriate to Train someone honesty. This research is a participatory action research.Research subjects that researchers carefully is the students of boarding school Al-HikmahSemarang. Implementation of research carried out through the stages of planning,implementation, observation and reflection. The research results obtained is the cultivation ofhonesty values through the media canteen honesty in boarding school Al-Hikmah Semarangeffective implemented. This is based on the results of research conducted on cycle I and cycleII. In cycle I can be seen that the santri honesty reaches 99% and in the second cycle thehonesty of the santri reaches 100%. Constraints faced in the cultivation of values of honestythat is associated with some students are still awkward with the sale system in the canteenhonesty, there are some santri who do not know the currency and difficult to determine thehonesty of each santri.Keywords: Honesty, Media, Honesty Cafeteria